Development of motor skills through movement games - Bitang, Andrei; Grosu, Vlad Teodor; Macarie, Anca; Lucian, Rodica; Bitang, Viorel (Arena-Journal of Physical Activities, 2023)
Introduction. The new requirements and conditions formulated by the development of society impose on the didactic process of physical education its enrollment in the idea of modernizing the activity, imposing a richer content and a complex methodology based on a deep knowledge of the level of development and growth of the organism at a given moment. The goal. In the paper, I set out to investigate whether the effort made in systematic and correctly dosed physical education lessons has the role of optimizing and perfecting the development process (physical, motor and mental) of the students’ bodies, as well as to find out whether the consistent practice of games of movement in the school activity (class and optional lessons) and independent activity contribute to strengthening the spirit of discipline and organization, to the easy practice of physical exercises performed with a greater effort in the lesson, as well as to the faster development of qualities motor skills (speed, skill, endurance, strength and mobility). The hypothesis. By using movement games in a rhythmic way within physical education lessons, after a judiciously elaborated planning, I believe that they will contribute essentially to the faster development of motor qualities (speed, skill, resistance, strength and mobility), to strengthening the spirit of discipline and organization, to a faster adaptation to the effort in the physical education lesson. Work methodology. The subjects are between 7-8 years old. The research took place over a period of 6 months, using two experimental and control groups. The initial measurements were carried out in the first semester (September 2022), and the final tests took place in February 2023. During the experiment, we used movement games, which gave a pleasant character to the physical education lessons. Results . Through the use movement games, lessons have become may pleasure and efficient, increasing the interest manifested by children in the the process instructive-educational. Conclusions. The movement games used in the physical education activity had a positive influence in obtaining the results of the experiment.